2010
DOI: 10.1590/s1516-35982010000600019
|View full text |Cite
|
Sign up to set email alerts
|

Características de carcaça e composição da carne de cordeiros terminados em confinamento com dietas com diferentes níveis de energia

Abstract: RESUMO -Avaliaram-se as características da carcaça, a composição tecidual da secção entre a 9 a e a 11 a costela, a composição centesimal do músculo longissimus dorsi e a proporção dos componentes não-carcaça de cordeiros terminados em confinamento com dietas contendo 1,49; 1,55; 1,62; ou 1,68 Mcal de energia líquida/kg de matéria seca. As dietas foram compostas de silagem de milho como volumoso e concentrado composto de um produto comercial e do suplemento energético Lacto Plus ® . Foram utilizados 16 cordeir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
1
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
2
1
1
1
Order By: Relevance
“…A bone yield similar to that found here (18%), though associated with a lower muscle yield (50.9%) and a much higher fat yield (30%) was found by Carvalho & Medeiros (2010) for a lower-quality carcass than was observed in this research.…”
Section: Resultssupporting
confidence: 85%
“…A bone yield similar to that found here (18%), though associated with a lower muscle yield (50.9%) and a much higher fat yield (30%) was found by Carvalho & Medeiros (2010) for a lower-quality carcass than was observed in this research.…”
Section: Resultssupporting
confidence: 85%
“…The average HCY (49.4 kg/100 kg SBW) found for non-castrated male lambs (¾ Texel + ¼ Pantaneiro) in our study was higher than that reported by Carvalho and Medeiros (2010) for non-castrated male lambs (½ Texel + ½ undefined; 47.4 kg/100 kg SBW). Lima et al (2013) also published HCY (48.7 kg/100 kg SBW) and CCY (47.2 kg/100 kg SBW) for male Texel lambs that were lower than those found in the present work.…”
Section: Discussioncontrasting
confidence: 84%
“…Therefore, the higher ADG of efficient animals may have resulted from lower maintenance energy expenditure in fat tissue synthesis. Lamb internal fat has no use for human consumption; thus, fat deposition directs energy away from the production of components with commercial value (Carvalho and Medeiros, 2010;Moreno et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…There were no significant differences in heart and respiratory organ weights between the four treatments, because these organs maintain its integrity due to the priority of nutrient utilization, independently of feeding. This effect was also observed by Carvalho and Medeiros (2010) who used diets with different energy levels the authors found no difference between treatments for organ weights. These results corroborate with those found by Cutrim et al (2012), this may likely be due to the similar age and initial and slaughter weights of animals.…”
Section: Resultssupporting
confidence: 71%